ANALISIS KEBUTUHAN MEDIA BERBASIS VIDEO SEBAGAI SARANA PEMBELAJARAN NILAI-NILAI EMPATI BAGI CALON GURU PENDIDIKAN AGAMA ISLAM - hafizah, Tia; Aulia Safitri, Suci; Ananda, Salsabilla; Fitria, Norhalijah Lira; Jasiah, Jasiah (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
This study aims to analyze the need to use Video-based Media as a means of learning empathy values in Islamic Religious Education (PAI). The background of this research is based on the low affective cultivation of empathy values in the learning process which is still dominated by conventional methods. The research method used is a mixed approach (mix method) with data collection techniques through Likert scale questionnaires distributed to 30 prospective PAI teacher students at IAIN Palangka Raya. The results showed that the level of urgency of learning empathy values reached 81.8% and the need for the use of video media amounted to 84.6%, both of which were included in the very high category. This finding confirms the importance of video-based learning media innovation in conveying religious values in a more contextual and emotional manner.